Application of Electrospun Gas Diffusion Nanofibre‐membranes in the Determination of Dissolved Carbon Dioxide. Issue 5 (26th February 2013) - Truong, Yen B.; O'Bryan, Yukie; McKelvie, Ian D.; Kyratzis, Ilias L.; Humphries, William; Kim, Il‐Doo
Abstract This study demonstrates the first time use of electrospun nanofibrous hydrophobic membranes as gas diffusion (GD) membranes in flow injection analysis (FIA) for the determination of carbon dioxide. Different electrospun membranes are prepared from polyvinylidene fluoride (PVDF) and polystyrene (PS) polymers. To impart structural integrity for PVDF membrane, the addition of 1, 4‐butanediol dimethacrylate (BDDMA) is used to form an interpenetrating network, while for PS membranes are spot welded with heat‐pressing at 80 °C. Heat pressed PS membranes are shown to have the best analytical sensitivity among other electrospun membranes and performed as well as the commercial PP membrane. A correlation is observed between the thickness of heat pressed PS membranes and analytical sensitivity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>